2012
DOI: 10.1111/1471-0528.12060
|View full text |Cite
|
Sign up to set email alerts
|

Decision aids to improve informed decision‐making in pregnancy care: a systematic review

Abstract: Background Rapid development in health care has resulted in an increasing number of screening and treatment options. Consequently, there is an urgency to provide people with relevant information about benefits and risks of healthcare options in an unbiased way. Decision aids help people to make decisions by providing unbiased non-directive research evidence about all treatment options.Objective To determine the effectiveness of decision aids to improve informed decision making in pregnancy care.Search strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 29 publications
5
110
0
3
Order By: Relevance
“…A passive flow of information from providers to users was not effective in improving users’ knowledge and awareness about their health condition for shared decision-making 30 40 41. The greatest benefits were observed when a decision support technique was implemented in the form of counselling from a care provider involving information, discussion of options and clarification of values 42. Two reviews found that regular frequent discussions with healthcare providers were more effective than a one-off contact 27 35.…”
Section: Resultsmentioning
confidence: 99%
“…A passive flow of information from providers to users was not effective in improving users’ knowledge and awareness about their health condition for shared decision-making 30 40 41. The greatest benefits were observed when a decision support technique was implemented in the form of counselling from a care provider involving information, discussion of options and clarification of values 42. Two reviews found that regular frequent discussions with healthcare providers were more effective than a one-off contact 27 35.…”
Section: Resultsmentioning
confidence: 99%
“…52,53 The findings of this study add to the growing clinical and epidemiologic evidence that prolonging pregnancy (increasing gestational age), even at term (from 37-38 weeks), can benefit brain 6 To support informed decisionmaking with their pregnancy care provider, it is important for women and their families to have readily available and accessible information about the optimal duration of pregnancy and any increased risk of poorer development or other adverse outcomes associated with early planned birth. 55 This information is relevant given recent research reporting that >90% of women indicated the earliest gestational age for safe delivery was before 39 weeks. 56,57 Furthermore, another study reported that almost half of women thought a cesarean delivery without medical indication should be performed upon request, despite minimal knowledge about the risks and benefits of one.…”
Section: Discussionmentioning
confidence: 99%
“…9 Information and decision aids have been recommended for use in clinical situations in which patient education is necessary for fully informed decision-making. [10][11][12][13] Use of decision aids for prenatal counseling using structured, paper-based or basic electronic tools has been associated with less decision conflict, improved knowledge, and in some cases, increased uptake of prenatal testing. [14][15][16][17][18] Such tools can facilitate an improved informed consent process, yet few decision aids have been developed and evaluated in the United States, particularly for use in low literacy populations.…”
Section: Introductionmentioning
confidence: 99%